2014
DOI: 10.1016/j.ijrobp.2013.09.051
|View full text |Cite
|
Sign up to set email alerts
|

A Phase 2 Trial of Stereotactic Radiosurgery Boost After Surgical Resection for Brain Metastases

Abstract: Purpose/Objective To evaluate local control following surgical resection and postoperative stereotactic radiosurgery (SRS) for brain metastases. Methods and Materials Forty-nine patients (50 lesions) were enrolled and available for analysis. Eligibility criteria included histologically confirmed malignancy with 1 or 2 intraparenchymal brain metastases, age ≥18, and KPS ≥70. Cox proportional hazard regression model was used to test for significant association between clinical factors and overall survival (OS)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
113
1
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 218 publications
(134 citation statements)
references
References 36 publications
15
113
1
5
Order By: Relevance
“…8,10,11 The timing of publication of these studies coincides with an observed increase in the uptake of SRS. During our study period, multiple institutional SRS series were published, demonstrating promising efficacy for up to, and beyond, 10 intracranial lesions, [20][21][22] in elderly patients, 23 and in the postoperative setting, 24 indicating an increased practitioner comfort level with brain SRS for a number of clinical situations.…”
Section: Discussionmentioning
confidence: 98%
“…8,10,11 The timing of publication of these studies coincides with an observed increase in the uptake of SRS. During our study period, multiple institutional SRS series were published, demonstrating promising efficacy for up to, and beyond, 10 intracranial lesions, [20][21][22] in elderly patients, 23 and in the postoperative setting, 24 indicating an increased practitioner comfort level with brain SRS for a number of clinical situations.…”
Section: Discussionmentioning
confidence: 98%
“…Several retrospective [42][43][44] and one prospective phase II trial 45 reported local control rates at 1 year around 80% (70%-90%) and a median survival of 10-17 months (class IIIa): this suggests that postoperative SRS is as effective as WBRT in achieving local control. An alternative approach is the use of SFRT, presumed to be associated with lower risk of radionecrosis in larger lesions.…”
Section: Stereotactic Radiosurgery/stereotactic Fractionated Radiothementioning
confidence: 99%
“…Both single- and multi-dose SRS have been looked at as potential methods for delivering focal RT to the resection cavity. Prospective and retrospective evaluations of single- and multi-dose SRS to the resection cavity after brain metastasis surgery revealed excellent local control rates [24,25,26,27]. …”
Section: Radiotherapymentioning
confidence: 99%